Digitalisasi arsip vital di PT Pertamina (Persero) - Ratu Soraya; Agus Rusmana; Neneng Komariah (Jurnal Informatio, 2022)
In the beginning, PT Pertamina (Persero) had controlled and well-managed archives, but in 2010 the management was out of control. Thus, PT Pertamina (Persero) had to digitize vital archives that can compile and determine documents and can comply with management regulations such as PP No. 8 of 1997 regarding company documents, PP No. 87 of 1999 concerning procedures for destroying company documents, and PP No. 88 of 1999 concerning the transfer of company documents to legalized microfilm. The research focuses on the techniques carried out by PT Pertamina (Persero) in digitizing vital records. The research method used is descriptive qualitative using interview and observation approaches, and the sources to be interviewed are archivists who are responsible for digitizing vital archives. In addition, data analysis obtained through three stages: data reduction, data presentation, and concluding. The research found that the existence of success in digitizing vital records carried out by PT Pertamina (Persero) through a series of applications, such as the initial stages, digitization actions, and the final process, so that the activity have impacts, such as, accessibility, efficiency, and effectiveness. From the results of this study, it can be concluded that in digitizing vital archives conducted by PT Pertamina (Persero) carrying out the seven initial stages, digitization actions, and the final process of digitizing vital records.